Actuating Single Nano‐Oscillators with Light. Issue 6 (1st February 2018) - Cormier, Sean; Ding, Tao; Turek, Vladimir; Baumberg, Jeremy J.
Abstract: Thermoresponsive polymers can be used to rapidly actuate individual nanoparticles forming nanomechanical oscillators. Such systems are realized here with poly( N ‐isopropylacrylamide) (PNIPAM)‐coated gold nanoparticles deposited on gold films, which have a strong optical response that can be dynamically tracked. Changes in temperature surrounding the nanoparticles result in the contraction or expansion of the PNIPAM coating, thereby displacing the gold nanoparticles up and down on the gold mirror. Particle oscillation is optically monitored via the spectral position of the coupled plasmon modes, achieving sub‐millisecond translocation speeds when actuated by light via plasmonic heating. These fast nano‐oscillators can also generate forces exceeding 1 nN with efficiencies already exceeding 1%, which makes them ideal prototypes for nanomachines. Abstract : A fast nano‐oscillating system composed of individual PNIPAM‐coated Au nanoparticles on a metal film that delivers directional forces exceeding 1 nN is demonstrated. These thermoresponsive devices can be actuated with light, achieving switching times of the order of microseconds, and can be used as nanomechanical devices and for low‐energy optoelectronic nanoswitching.